Defect study during defect liability period / Mohd Asrul Hassin - Hassin, Mohd Asrul (2010)
Malaysia is one the fastest growing developing nation in the region and the world. In order to remain at pace, the government had planned and budgeted billions of Ringgit to ensure the flow of projects in Malaysia. From the report and the problem statement in the newly completed project, government made the modification in the practice the Defect Liability Period. Government extended from the normal Defect Liability Period 12 months to 24 months. The reason why government extended the Defect Liability Period because to give the opportunity to clients or building owner make the report on the defect occur in their building. A study was conducted to identify the types o f defect, categories o f defect and how critical o f defects occurred during Defect Liability Period. A total o f 50 questionnaires were distributed to contractor, consultant, developer and building owner. The study indicated that defects are due to faulty design, faulty construction, faulty material and faulty use. The 4 groups o f defects mentioned above are main causes o f defects. The most group critical o f defect is faulty use in questionnaire result. Conditionsurvey indicated the faulty construction is the higher critical o f defects occurred during Defect Liability Period.